Multimedia Development of Android Based Mathematics Learning in Elementary School Students - Rahmah Kumullah; Khaerun Nisa'a Tayibu (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2021)
This research uses a research and development (R&D) approach. by adapting Alessi and Trolip's development model, namely (1) planning, includes: problem analysis and needs analysis, (2) Design, includes: manufacture flowcharts, storyboards, and interface design, (3) the media development stage, includes material gathering, product manufacturing, code writing, alpha testing, revisions, and beta testing. Data collection tools used were questionnaires, data obtained then analyzed by quantitative descriptive techniques. The research results note that: (1) multimedia development results mathematics learning in the form of an android application with the format * .apk, (2) online general multimedia learning developed is very suitable for use as learning support with an eligibility percentage of 83.34% of the experts media, 70.5% from material experts, and 92.9%, from users, and (3) completeness of the results student learning after using multimedia learning mathematics very much good, which is 80%, thus it can be concluded that the application has a positive impact on student learning outcomes.